Pelatihan Pembuatan POC Daun Kirinyuh (Chromolaena odorata) dalam Mewujudkan Pertanian Organik Ramah Lingkungan di Kelompok Wanita Tani Sehati Desa Magepanda Kecamatan Magepanda - Blasius Subirno; Gabriel Otan Apelabi; Yovita Yasintha Bolly (Prima Abdika: Jurnal Pengabdian Masyarakat, 2026)
This community service activity aimed to empower the Sehati Women Farmers Group in Magepanda Village through training on the production of Liquid Organic Fertilizer (LOF) derived from Kirinyuh leaves (Chromolaena odorata). The activity was motivated by farmers' high dependence on chemical fertilizers, which are relatively expensive and can degrade soil fertility over the long term. Meanwhile, Kirinyuh weeds, which are abundantly available in the surrounding environment, have not been optimally utilized. The implementation method consisted of preparation, material dissemination, practical demonstrations of LOF production, and evaluation. The LOF production process involved fermenting Kirinyuh leaves with the bioactivator EM4 and molasses. The results indicated an 80% increase in the partners’ knowledge and skills in processing weeds into value-added fertilizer. The participants were able to carry out all stages of liquid organic fertilizer production, from material chopping to fermentation, in accordance with established procedures. The training on producing Kirinyuh leaf-based LOF proved effective as an alternative for providing an economical and environmentally friendly fertilizer, while also supporting the implementation of sustainable agricultural systems in Magepanda Village.